"Where does my menstruation come from?" Experiences and costs of menstrual hygiene management among Rwandese school girls. - Kirsten Beata Dodroe; Lilian Nantume Wampande; Arlene Nishimwe; Mutesi Mukinisha; Janna M Schurer (PLOS Global Public Health)
The Government of Rwanda recently instated a minimum menstrual hygiene management (MHM) package for all schools; however, coverage is not universal, and there remains little information on the availability or financial burden of MHM resources in rural and remote areas. This study sought to describe Rwandese secondary school girls' perceptions and practices of MHM, their financial costs, and their access to MHM related infrastructure and products. A mixed-methods survey was conducted in three phases, namely (1) a quantitative questionnaire (2) a qualitative 'Jar Voices' activity, and (3) an observational Water, Sanitation and hygiene (WASH) checklist. One Lower Secondary School (LSS) of each type (private, public and government-aided) was randomly selected from each of Rwanda's five provinces, and all LSS2 and LSS3 girls who reached menarche were invited to participate. Overall, 1,117 girls participated, including 351 (31.4%) from public schools, 543 (48.6%) from government aided schools and 223 (20.0%) from private schools. Only 35.7% of the girls correctly identified the origin of menstruation. The main source of information on menstruation was mothers. Most girls (82.5%) used single-use sanitary pads, and a small proportion (14.6%) relied on reusable cloth pads. The most identified barriers to accessing sanitary products were financial barriers. The average cost of menstrual products per cycle varied between RWF 3,100 in private schools, to RWF 4,000/4,300 in public/government-aided schools, and were covered mainly by parents. Most schools had gender-sensitive sanitation facilities, mainly pit latrines (86.7%), but only 53.3%, 33.33% and 20% provided water, soap and MHM commodities respectively. The results underscored the need for continuous menstrual education aimed at both girls and parents, and capitalizing on low-cost initiatives that can improve access to sanitary pads and WASH/sanitary facilities in schools.